Emissions into the Air from Bitumen and Rubber Bitumen—Implications for Asphalt Workers' Exposure. Issue 7 (21st June 2018) - Nilsson, Patrik T; Bergendorf, Ulf; Tinnerberg, Håkan; Nordin, Erik; Gustavsson, Mats; Strandberg, Bo; Albin, Maria; Gudmundsson, Anders
Abstract: The risk among asphalt workers of developing adverse health effects may increase due to their occupational exposure. One area of special concern arises when rubber granules are mixed into bitumen to enhance asphalt properties. This research characterizes and compares bitumen and rubber bitumen regarding the emissions of and workers' exposure to particulates, polycyclic aromatic hydrocarbons (PAHs) and benzothiazole. A laboratory and a field study were carried out. In the laboratory, two types of bitumen, one with and one without rubber, were heated up to two temperatures (140°C and 160°C). The concentrations and chemical compositions of the emissions were determined. In the field at asphalt work sites, both emissions and worker exposure measurements were performed. The methods applied included direct-reading sampling techniques next to the asphalt work area and personal sampling techniques on asphalt workers. The exposure measurements on asphalt workers for respirable dust, total dust, particle number and mass, and total PAH concentrations showed similar concentrations when both standard and rubber bitumen were used. The asphalt-surfacing machine operators were the workers with the highest observed exposure followed by the screed operators and roller drivers. Both laboratory and field measurements showed higher concentrations of benzothiazole when rubber bitumen was used, up to 7.5 times higher in the laboratory. The levels of naphthalene, benzo(a)pyrene, and total particles were lower for both types compared with the Swedish occupational exposure limits, 8-h time weighted average concentrations. Benzo(a)pyrene exceeded however the health-based guideline value given by the WHO for both types of bitumen. The study concludes that several air pollutants such as benzothiazole and PAHs are emitted into the air during asphalt work, but it is not evident if exposure to rubber bitumen possesses a higher risk than exposure to standard bitumen in terms of asphalt worker exposure.